61.6k views
4 votes
X+3y=-2
3x+4y=-6
USE SYSTEMS BY SUBSTITUTION.

X=
Y=

2 Answers

3 votes

Answer:

X=-2

Y=0

Explanation:

X+y=-2 = x=-2-y

3x+4y=-6

3(-2-y)+4y=-6

-6-3y+4y=-6

y=0

x+3(0)=-2

x=-2

User Mavrosxristoforos
by
4.6k points
2 votes

Answer:


\boxed {\boxed {\sf (-2,0)}}

Explanation:

To solve by substitution we must first isolate 1 variable in an equation.

Let's use the first equation.


x+3y= -2

Subtract 3y from both sides to isolate the variable x.


x+3y-3y= -2 -3y


x= -2 -3y

Now we can substitute the expression (-2-3y) in for x in the second equation.


3x+4y= -6


3(-2-3y)+4y= -6

Distribute the 3. Multiply each term inside the parentheses by 3.


(3*-2)+ (3*-3y)+4y=-6\\-6-9y+4y=-6

Combine the like terms on the left side.


-6-5y= -6

Add 6 to both sides to isolate the variable.


-6+6-5y=-6+6\\-5y=0

Divide both sides by -5.


-5y/-5=0/-5 \\y=0

Now we know that y is equal to 0 and can substitute it into the first equation and find x.


x+3(0)=-2


x+0=-2 \\x= -2

x is equal to -2 and y is equal to 0.

User Dwmcc
by
4.7k points